Із досліджень над хрематонімією. Зауваження щодо назв польських та українських футбольних команд - Олейнік, Марек; Olejnik, Marek (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано значення деяких польських та українських назв футбольних клубів, які в останні роки виступали в Прем’єр-лізі обох держав. Назви клубів поділені на кілька груп: які походять від назв країн, провінцій, міст, регіонів, річок; від назва військових відділень та політичних формацій; які символізують історичні постаті; які походять від знаків, символів, професійних назв; назви, перший компонент яких є буквеним скороченням (абревіатурою), а другий – назвою міста; назви, пов’язані з машинами, апаратами (покликані показати енергію, силу); які походять від астрономічних явищ; які походять від назв спонсорів. Аналіз продемонстрував, що назви клубів польської та української Прем’єр-ліг, різні щодо їхньої мотивації. Половина назв клубів польської Екстракласи – лексеми, що походять від назв країн, провінцій, міст, регіонів, річок. Майже половина (7 назв) таких команд наявна і в українській лізі. 4 команди в Україні мають професійні назви, а в Польщі це лише «Гурнік» (Забже). In the article there was carried out semantic analysis, with presentation of etymology of names of selected Polish and Ukrainian football clubs playing during last few years in the first divisions of both countries. The clubs’ names have been grouped into following categories: deriving from the names of countries, provinces, cities, regions, rivers; deriving from the names of military units and political formations; created from the names of historical personage; deriving from signs, symbols; names of professions, names where the first component is acronym and the secondone is the name of city; names related to machines, apparatus (showing energy, power); coming from astronomical phenomenon; coming from personal names; deriving from names of sponsors. Analysis proved that the names of Polish and Ukrainian first divisions football clubs are diversified regarding motivation. Half of the names of clubs of Polish first division comes from the names of countries, cities, regions and rivers. Almost half of Ukrainian first division football clubs (7 clubs) has got such names. 4 names in Ukrainian first division comes from the names of professions. In Polish first division there is only one such name: Górnik (Miner) Zabrze.
From Studies on Chrematonymy. Comments to the Names of Polish and Ukrainian Football Clubs
Keywords: мовознавство; ономастика; хрематонімія; назви футбольних клубів; футбол; linguistics; onomastics; chrematonymy; names football club; football